Repeatability of central corneal thickness measurement with the Pentacam HR system - Alonso,Ruiz Simonato (2012)
PURPOSE: To assess the repeatability of central corneal thickness measurement at the geometrical center (Central Corneal Thickness - CCT) given by the Pentacam High Resolution (HR) Comprehensive Eye Scanner (Oculus, Wetzlar, Germany) over time. METHODS: Prospective, single center, observational study. Two separate CCT measurements were taken by the Pentacam corneal tomography exam (CTm) 3 to 12 months apart, and compared. RESULTS: One hundred and sixteen eyes (n=116) of 62 health patients were included in this study. Average CCT in first and last visits was 541.6±37 µm and 543.6±36.9 µm respectively. Mean difference between both measurements was 9.2±6.4 µm, and there was no statistically significant difference in CCT measurement between visits, with good correlation between them (P = 0.057, r² = 0,9209). CONCLUSION: Pentacam (HR) CTm gives repeatable CCT measurements over time.